ERGONOMIC DESIGN RECOMMENDATIONS FOR DESIGNING AN OPTICAL FIBER RESCUE SIGNAL TO LIFE JACKET - Tjolleng, Amir; Chang, Joonho; Jeong, Lewis; Kim, Minji; Jung, Kihyo (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
An optical fiber can be used as a rescue signal on a life jacket to improve visibility and user acceptability. This study addressed three ergonomic design issues (rescue signal location, light intensity and color, and button location) that require applying an optical fiber into the design of life jacket’ rescue signal. The rescue signal location was suggested by a scenario analysis of life jacket use in emergency situations. The light intensity and color required for producing a visual sensation were investigated by a literature review on human perception. Lastly, the proper locations of a power button were examined in terms of pressing forces and preference. The experimental results showed that the buttons on the left side of a life jacket had 18% to 20% smaller peak and mean pressing forces. In addition, most of the participants (50%) preferred the upper-left chest area for a power button than other locations.